Analysis of the Performance of Tongkonan Traditional House Structure Against Earthquake Loads - Ampangallo, Bastian A.; Honta, Zwengly Lodi; Manga, Jufri (ASTONJADRO, 2026)
The Tongkonan building in Toraja is one of many structures in the archipelago that possesses a unique form, structure, and construction. The traditional house of the Toraja tribe located in South Sulawesi Province is called the Tongkonan. This building is made of wood. The traditional house differs from other traditional houses in terms of its structural system, making the Tongkonan a very interesting subject for research. Along with the advancement of time, it is important to study and analyze the structure of Tongkonan in order to enhance its resilience to earthquakes. This research aims to analyze the behavior of the Tongkonan structure under earthquake loads. The structure of the Tongkonan house is modeled in SAP2000 software to obtain the internal forces acting on the structural elements of the Tongkonan house. Then an analysis was conducted on the beam section, resulting in the internal force analysis occurring within the structure. The internal forces of the Tongkonan structural elements refer to the principles of tension and compression members, beam-columns, and flexural members, depending on the internal forces acting on each element. The results of the structural modeling analysis show that Tongkonan I is more resistant to earthquakes, with a minimum axial value of –1385.74 kN, a maximum axial value of 204.14 kN, a minimum shear value of –719.82 kNm3, and a maximum shear value of 719.82 kNm3. Meanwhile, Tongkonan II has a minimum axial value of –1550.31 kN, a maximum axial value of 457.67 kN, a minimum shear value of –813.23 kNm3, and a maximum shear value of 813.24 kNm3.